Assessment of SIMBox Fraud: An Approach to National Security Threat - N. Kala (Innovations in Science and Technology Vol. 1, 2021)
SIMBox fraud is one of the most sophisticated fraud types in the recent times. Telecom regulators and mobile operators are facing massive revenue losses as bypass fraud continues to be one of the most prolific and costly frauds. To terminate international inbound calls to local subscribers, gateway equipment such as fixed, Voice over Internet Protocol (VoIP), Global System for Mobile Communication (GSM), Code Division Multiple Access (CDMA), VOIP to GSM, and fixed line gateway are used. Fraudsters bypass the connections by diverting traffic away from legal interconnect gateways. Fraudulent Operators sending outbound international traffic connect to interconnect operators with lower rates, leading to loss of revenue for the original internet service provider. SIMBox fraud is considered illegal since those who undertake it are not licensed to provide telecommunication services. SIMBox fraud is also considered as a national security threat since terrorist groups use this device to make international calls at local call rates. The main objectives of this study is to provide background of cellular networks, internet gateway, voice over internet protocol, preliminary overview to SIMBox architecture, internet bypass fraud - including GSM gateway fraud and SIMBox fraud and the State-of-Art Procedures to combat SIMBox fraud. This chapter focuses on the study of SIMBox fraud as a National Security threat. Further this study also suggests the methods for mitigating such security threat and the next generation forensic detection methods.